2014
DOI: 10.1002/cne.23495
|View full text |Cite
|
Sign up to set email alerts
|

The eyes of lanternfishes (Myctophidae, Teleostei): Novel ocular specializations for vision in dim light

Abstract: Lanternfishes are one of the most abundant groups of mesopelagic fishes in the world's oceans and play a critical role in biomass vertical turnover. Despite their importance, very little is known about their physiology or how they use their sensory systems to survive in the extreme conditions of the deep sea. In this study, we provide a comprehensive description of the general morphology of the myctophid eye, based on analysis of 53 different species, to understand better their visual capabilities. Results con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Even though L. parvicauda possesses adaptations to enhance photon capture over the whole retina (i.e. circumlental aphakic gap and tapetum lucidum) [de Busserolles et al, 2014a], these findings indicate that this species possesses a less specialized visual system than the 2 other species mentioned above. Wagner [2001] investigated brain areas in mesopelagic fishes and showed that different myctophid species rely more or less heavily on different sensory systems.…”
Section: Ecological Significance Of the Retinal Specializations In Lamentioning
confidence: 48%
See 2 more Smart Citations
“…Even though L. parvicauda possesses adaptations to enhance photon capture over the whole retina (i.e. circumlental aphakic gap and tapetum lucidum) [de Busserolles et al, 2014a], these findings indicate that this species possesses a less specialized visual system than the 2 other species mentioned above. Wagner [2001] investigated brain areas in mesopelagic fishes and showed that different myctophid species rely more or less heavily on different sensory systems.…”
Section: Ecological Significance Of the Retinal Specializations In Lamentioning
confidence: 48%
“…6 ). The area temporalis found in D. mollis (this study), associated with the presence of a nasal aphakic gap [de Busserolles et al, 2014a], provides the potential for binocular vision ( fig. 6 ) and may enhance acuity directly in the illuminated region in front of the fish, a powerful predatory strategy.…”
Section: Ecological Significance Of the Retinal Specializations In Lamentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbance spectra (330-800 nm) were made using a computer-controlled single-beam wavelength-scanning microspectrophotometer [Hart et al, 2004[Hart et al, , 2011[Hart et al, , 2012. Due to the very small diameter of the rod photoreceptors of the lanternfish species analysed (<1 μm [de Busserolles et al, 2014b]), longitudinal 'endon' absorbance spectra were measured from patches of rod outer segments. A sample scan was made by aligning the measuring beam (typical dimensions 10 × 10 μm) within a patch of rods in a specific part of the retina and recording the amount of light transmitted at each wavelength across the spectrum.…”
Section: Microspectrophotometrymentioning
confidence: 99%
“…We used visual pigment templates [Govardovskii et al, 2000] of appropriate λ max for the modelling. Normalised absorbance templates were converted to axial outer segment absorptance by assuming a visual pigment specific (decadic) absorbance of 0.013 μm -1 (rhodopsin [Turner et al, 2009]) and a rod outer segment length of 39 μm for S. evermanni [de Busserolles et al, 2014b] and 45 μm for M. obtusirostre as per a similar species ( M. brachygnathum [de Busserolles et al, 2014b]). Measurements of ocular media transmittance could not be made from fresh specimens at sea and so were excluded from the modelling.…”
Section: Spectral Tuning In Lanternfishesmentioning
confidence: 99%